The Core Knowledge Management for Bus Operators at Bangkok Mass Transit Authority (BMTA) - Nuchkong, Vasin; Chunhasiwong, Kitti (Interdisciplinary Academic and Research Journal, 2023)
Knowledge is the most valuable asset of an organization. It is infinitely different from other assets in the organization, the more it is used, the greater its value. The more knowledge an organization has, the newer things it learns. By learning more, more new knowledge can be created. Therefore, knowledge is important to be preserved and transmitted. To extend knowledge into new knowledge that is up to date with the changes of the global society and can be used in time when needed. to achieve the operational goals of the organization. The purpose of this study is to 1) Study the necessary knowledge components for bus operators of the Bangkok Mass Transit Authority. 2) Create a guideline for knowledge management of commuter operators at the Bangkok Mass Transit Authority. This research is mixed (Mixed methods). The sample consisted of 1,360 Bangkok Mass Transit Authority bus operators. The size was determined using a sample-variable ratio of 20:1, representing 20 times the analytical variable. which is by the range specified by (Hair et al.) The confidence value is 0.95. The instrument used was a 5-point questionnaire with a reliability of 0.95. Data were analyzed by statistical frequency, percentage, mean, and factor analysis. The research results showed that 1) The necessary knowledge components for bus operators of the Bangkok Mass Transit Authority are: (1) Knowledge of the characteristics of train operators (2) knowledge of the operation process of the bus operation (3) knowledge of relevant laws (4) knowledge of problem-solving skills (5) Organization knowledge (6) Knowledge of corporate culture (7) Knowledge of Service Theory (8) Knowledge of the organization’s operational guidelines (9) knowledge of communication technology 2) Guidelines for knowledge management of bus operators at the Bangkok Mass Transit Authority found that (1) Knowledge is created and sought by synthesis of knowledge from workers who are close to retirement. (2) have training (3) Most employees keep their knowledge to themselves. (4) Exchanging knowledge or extending knowledge through self-learning from work. (5) Disseminate knowledge by telling, discussing, and exchanging experiences in the employee community.